PENGARUH PEMEKATAN KONSENTRASI FENOL DARI LINDI HITAM DALAM PEMBUATAN PEREKAT FENOL FORMALDEHIDA - R Sudradjat; E Yusnita; U Kulsum; E Kusmiati (Pusat Penelitian dan Pengembangan Hasil Hutan, 2003)
This investigation was a successive series of experiments aimed at assessing the manufacture of phenol formaldehydeglue utilized the black liquor from soda-process-based pulp mill.At first, the phenol in the black liquor was concentrated by adding crystal phenol. The ratios in weight between crystal phenol as added and black liquor were consecutively 1:5, 1:10, 1: 15, 1:20, and 1:25, and as such yielded the concentrated phenol in the liquor at four levels as well.The results revealed that efficiency recovery of phenol obtained by vacuum distillation was 12 percent. Such efficiency was because most of the phenol in black liquor was associated with other elements in the lignin structure or other compounds. The phenol was further reacted with formaldehyde, and the resulting phenol formaldehyde (PF) used as glue in plywood bonding.Results revealed that moisture content of plywood with PF glue where the phenol was from the mixture of concent tended black liquor's phenol and crystal phenol varied at 8.80 to 9.61 percent. The moisture contended to increase with the increase in the ratio of crystal phenol to the black liquor distillate.The density of plywood was about 0.5710 - 0.6431 gram per cm3, and tended to increasewith the increase in the ratio of crystal phenol as well. •The bonding strength of plywood without boiling-treatment was in the range of 11.173-23.722 kg per cm2, where by the lowest strength occurred at implementing 1 : 20 ratio (A4) and the highest at 1 : 5(A1). Meanwhile, the bonding-strength test with boiling-treatment revealed the value at 1.924 - 18.306 kg per cm2 in that the lowest value was at 1 : 25 ratio (A5) and the highest at 1 : 5 ratio (Al).